Consumer Legal Protection in Drinking Water Refill Depot - zulkifli adenga (Universitas Negeri Gorontalo, 2019)
Abstract: This study aims to determine the application of product quality standards for refilling drinking water in the East City of Gorontalo City and to find out the form of legal protection for consumers in the use of drinking water depots. The researcher uses a type of normative research that includes legal principles, legal systematics and legal comparisons and is supported by empirical research through primary data sources, namely data based on information obtained directly at the research location. The results showed that the fulfillment of the Quality Standards for Drinking Water Depots in Gorontalo City was not fully appropriate, one of which was in fulfilling the certification issued by the local government in ensuring hygiene and sanitation at least once a year. The form of legal protection for consumers is carried out by the Health Service in supervising and applying administrative sanctions to the management of drinking water depots.Keywords: Legal Protection, Consumers, Water Depot.